Pengaruh Customer Experience Dan Cash Back Terhadap Keputusan Konsumen Bertransaksi Melalui E’commerce Tokopedia Pada Masa Lockdown Pandemi Covids 19 Di Kota Banjarmasin - Nuryadin, Muhammad Teguh; Padli, Padli; Anwar, Hairul (POSITIF : Jurnal Sistem dan Teknologi Informasi, 2021)
This study aims to determine and analyze whether Customer and Cash Back Experiencehave a simultaneous and partial effect on consumer decisions to transact through E'Commerce Tokopediaduring the Lockdown Pandemic Covid-19 in Banjarmasin. This type of research is quantitative descriptive with multiple linear regression analysis with the help of software. SPSS analyzed from primary data totaling 100 respondents who were taken using themethod stratified judgment sampling to the people of Banjarmasin who actively transact through the marketplace. The results of this study indicate that there is a simultaneous significant influence of Customer Experience and Cash Back on consumer decisions to transact via E-Commerce Tokopediaduring thePeriod Lockdown Pandemic Covids 19 in Banjarmasin City. While partially, only the Customer Experience variable has a significant influence on consumer decisions to transact via E-Commerce Tokopediaduring thePeriod Lockdown Pandemic Covids 19 in Banjarmasin City